Effect of dried bakery powder with and without yeast in the diet on some productive traits of broilers Ross 308. - Hanin R.A.M. Al-Abrahimi; Muhammad J. Shahid (University of Thi-Qar Journal of agricultural research, 2022)
This experiment was conducted to find out the effect of replacing two levels of dried bakery with and without yeast instead of the wheat and barley on the productive performance of Ross 308 broilers. At the poultry field, for the research station, College of Agriculture and the Marshes, Thi Qar University, from 11/8/2020 to 12/12/2020, using 270 unsexed one-day-old broiler chicks, were randomly distributed over five experimental treatments and three replicates (18 birds/replicate). The treatments were as follows: T1: control treatment without addition, T2 and T3 added 10 and 20% dried bakery powder without yeast, T4 and T5 added 10 and 20% dried bakery powder with 0.04% yeast. The results of the study indicated that there was a significant (P≤0.05) improvement in the studied productive traits (Body weight, weight gain, feed intake, food conversion factor, mortality, vital ratio, and production index) for broilers, when added dried bakery powder with yeast, the best addition ratio was 20% dried bakery powder with 0.04% yeast compared to the control treatment and treatments for added dried bakery powder without yeast. Keywords: dried bakery powder, yeast, productive traits, Ross 308 broilers.